Quality and productivity improvements using industrial engineering (IE) tools ... [at al.] / [microfilm] - 277431 Chen, Chin Ee (Skudai : Universiti Teknologi Malaysia, 1999)
Project Paper (Bachelor of Engineering (Mechanical) - University Teknologi Malaysia, 1999